2015
DOI: 10.1109/tie.2015.2405057
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of SiC Power Devices for High-Performance Domestic Induction Heating

Abstract: This paper presents a comparative evaluation of silicon carbide power devices for the domestic induction heating application which currently has a major industrial, economic and social impact. The compared technologies include MOSFETs, normally-on and normally-off JFETs, as well as BJTs. These devices have been compared according to different figures of merit evaluating conduction and switching performance, efficiency, impact of temperature as well as other driving and protection issues.In order to perform the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It is now evident that the existence of this gate channel creates reliability challenges [1] especially at higher temperatures [2]. This worsens when silicon carbide (4H-SiC) is used to fabricate the devices [3]. BJTs inherently do not have gate oxide and therefore do not suffer from the oxide reliability issues or reduced channel mobility due to lower carrier concentrations in the cannel [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is now evident that the existence of this gate channel creates reliability challenges [1] especially at higher temperatures [2]. This worsens when silicon carbide (4H-SiC) is used to fabricate the devices [3]. BJTs inherently do not have gate oxide and therefore do not suffer from the oxide reliability issues or reduced channel mobility due to lower carrier concentrations in the cannel [4].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to provide a versatile large-signal high-frequency arbitrary waveform generator taking advantage of the new wide bandgap (WBG) devices [19][20][21][22] and a multi-level topology [23][24][25]. Multi-level converters have been studied and applied in the past to related applications such as pulsed electric fields for water disinfection [26][27][28][29][30], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the power device should be able to work at high frequency with low total losses and work in higher temperature. Nowadays, studies have shown the advantages of wide band-gap power devices in comparison with silicon devices [1]- [3]. The new progress in power devices technology establishes that silicon carbide (SiC) technology, and Gallium Nitride (GaN), are the solutions for the needs faced by power converters nowadays [4].…”
Section: Introductionmentioning
confidence: 99%